Doing, planning, "planning-doing:" a case of municipal pragmatism in collaboration with a university during the COVID-19 pandemic - Helvo Slomp Junior; Karla Santa Cruz Coelho; Delba Machado Barros; Tulio Batista Franco; Kathleen Tereza da Cruz (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
This article critically analyzes local governments' abilities to face the COVID-19 pandemic by examining an instance of technical-scientific cooperation between a municipality and a university located in the northern Rio de Janeiro (state) beginning in April 2020. This collaboration included: the implementation of a situation room, data processing and analysis for decision making and for public communication, a telemonitoring center, ongoing training with territorial healthcare teams, and an epidemiological study of COVID-19 in the municipality, among other actions. We situate our analysis within a conceptual framework that adopts a micropolitical view of concepts such as experience, pragmatism, "live work in action," and desire. The notion of "planning-doing" is deployed as an inventive form of planning that is only narrated a posteriori, as an imperative act, a live government in action that depends on the movement of desire oriented by life, and that only takes place in collective spaces of management practices and health care.